"Golden reality" or the "reality of gold": Artisanal mining and socio-environmental conflict in Chinapintza, Ecuador. Issue 1 (January 2016) - Sánchez-Vázquez, Luis; Espinosa-Quezada, María Gabriela; Eguiguren-Riofrío, María Beatriz
Highlights: We aim to determine population perception of socio-environmental conflicts in Chinapintza artisanal gold mining area. These conflicts are mainly related to the regularization process and obtaining the mining claim. Operative artisanal mining activities in Chinapintza help strengthen the identity and favour the social movement of the miners. We highlight the need to redefine the legal framework for artisanal mining and promote training processes in order to reduce the conflict associated to this activity. Abstract: Ecuador has long tradition of artisanal mining, mostly associated with environmental impacts and socio-environmental conflict. This article analyses the case of Chinapintza district, located in the area bordering Peru in the south east of the country. The miners in this area aim to obtain the "título minero" (mining claim) in order to regularize their situation to improve their conditions, and therefore reduce the social and environmental problems associated with their occupation. In this context, the main objective of this study is to determine how the population perceives the different socio-environmental conflicts of the Chinapintza area, and to characterize the difficulties encountered by artisanal miners in their efforts to organize and regularize their activities according to new legislation. Our main findings confirm the need to redefine the legal framework for artisanal mining and promote training processes for the workers in order to reduce socio-environmental conflicts.